REVIEW DEDUCTION INCOME TAX 21 BASED IMPLEMENTATION OF TER 2024 AND THEIR IMPLICATION ON CASH FLOW - Tjahjono, Josephine Kurniawati (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2024)
TER (Average Effective Rate) is likely to become more common in the field of taxation due to recently issued tax regulations related to Income Tax Income Tax 21 withholding. Income Tax 21 withholding has undergone multiplechanges, reporting procedures, and other aspects. The Term TER was created to complement PMK No. 168 of 2023, which concisely simplifies of calculation of Income Tax 21 withholding. The purpose of implementing TER is as follows: provide convenience for employers in calculating Income Tax Article Income Tax 21 to reduce the possibility of miscalculation. This paper seeks to demonstrate that the total amount of Income Tax withholding 21 before and after TER must be equal. However, the commotion that occurs in society, especially among employees, is the increase in the Income Tax 21 withholding tax rate deduction, which means decreasing their salary. The TER terms mentioned in PMK No. 168 of 2023 do not increase the tax burden. This is because the basis calculation income tax still refers to State Law No. Ps. 17 of 2023. The income tax calculation still follows the provisions of State Law Ps. 17 in general. The difference in deduction on Income Tax 21 withholding between the old way and TER basis system even in general makes the employee enjoy any less deduction than before and even can create the employee’s cash flow, which should increase their purchasing power. This policy is effective for income above Rp. 20 million monthly on average.